Sympoiesis ‘becoming with and through each other’: Exploring collaborative writing as emergent academics - Collett, Karen; van den Berg, Carolien; Verster, Belinda (Critical Studies in Teaching and Learning, 2023)
This paper explores our journey as three female academics as we collaboratively engage in the process of writing for scholarly publication. We read our experience through a Political Ethic of Care, Slow scholarship, and Sympoiesis. Informed by Barad’s (2007) relational ontology of space~time~mattering we explore our process of collaborative writing. We trace our journey as emerging scholars in different environments and through different modalities and material entanglements. The paper contributes to an understanding of how emerging academics find and create opportunities to develop their scholarly practice through collaborative sympoietic relationships. We show how through an engaged and sustained Slow scholarship we were able to claim space and time to enliven our creativity and joy. This empowered us to meaningfully assert ourselves within the context of a neoliberal academic environment and to reimagine how socially just practices of scholarly writing could be realised in the‘belly of the beast’.